2017
DOI: 10.12691/wjac-5-1-1
|View full text |Cite
|
Sign up to set email alerts
|

Ordinary Least Squares with Laboratory Calibrations: A Practical Way to Show Students that This Fitting Model may Easily Yield Biased Results When Used Indiscriminately

Abstract: Analytical calibration using ordinary least squares (OLS) is the most widely applied response function for calibration in all type of laboratories. However, this calibration function is not always the most adequate and its indiscriminant use can lead to obtain biased estimates of unknowns. Students need to be taught about the practical requirements needed to obtain good results with OLS and when this fitting method is not accurate. Different experimental calibration curves were obtained in laboratory sessions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 20 publications
1
12
0
Order By: Relevance
“…However, despite the fact that many researchers often do not take it into account, heteroscedasticity is more frequent than might be expected in experimental sciences. Many analytical methods yield non-constant variances over the calibration range [8,26,27,[30][31][32][33][34], as was the case with the calibrations evaluated in the present study ( Figure 1). In these conditions, the absolute errors of the instrument tend to be proportional to the concentrations, and the relative standard deviation is the constant parameter across the curve instead of the standard deviation [33,[35][36][37][38].…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…However, despite the fact that many researchers often do not take it into account, heteroscedasticity is more frequent than might be expected in experimental sciences. Many analytical methods yield non-constant variances over the calibration range [8,26,27,[30][31][32][33][34], as was the case with the calibrations evaluated in the present study ( Figure 1). In these conditions, the absolute errors of the instrument tend to be proportional to the concentrations, and the relative standard deviation is the constant parameter across the curve instead of the standard deviation [33,[35][36][37][38].…”
Section: Discussionsupporting
confidence: 58%
“…Previous studies have found that the variances obtained at low concentrations with WLS are significantly reduced when compared to OLS, and that precision loss with OLS calculations can be as high as one order of magnitude in the lower range of the calibration curves [32,[35][36][37]. The results obtained in the present study show that in 17 calibrations s b0 values determined by WLS were significantly smaller (2-23 times, p < 0.05, Fisher F-test) than by OLS (Tables 1-4), which agrees with the results obtained by other studies comparing OLS and WLS with experimental calibrations involving heteroscedastic data [8,26,27,47].…”
Section: Discussionmentioning
confidence: 97%
“…The most used linear regression function, OLS, is based on the minimization of the SSE term (also known as residuals) because this model was developed with the assumption that absolute errors of the dependent variable (measured as SD or variance, SD 2 ) are constant all along the range studied (homoscedasticity). However, in analytical and bioanalytical calibrations the most common situation is that absolute errors are not constant (heteroscedasticity) and the parameter that remains approximately constant is the relative error (RE; RSD) [6,[8][9][10][11][12][13]. In this situation, OLS regression overestimates the effect of calibrators at high concentration ranges, and the higher variations at this level have a much greater influence on R 2 than small deviations present at low ranges [14].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that when the data have a proportional error, neglect of weighting can increase the uncertainty by a factor ≥10 at the lower concentration level [15,16]. For these reasons, it has been reported that OLS should not be used when samples are expected to be determined close to the LOQs [1,[6][7][8][9]12,13,15,[17][18][19], as is very common in trace analysis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation